2009
DOI: 10.1097/pai.0b013e31818935a9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers in Thyroid Fine-needle Aspiration Biopsy

Abstract: With the combined use of HBME-1 and galectin-3 in indeterminate FNABs, a 10% increase in sensitivity is achieved. These markers show excellent sensitivity and specificity and may improve patient's selection for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…The reported data demonstrated that the combined use of markers had a better sensitivity and specificity than using each of the markers separately. This may help distinguish indeterminate or suspicious samples with a low or high risk of malignancy, thereby enabling a more adequate surgical selection [52][53][54][55]. Fadda et al and Rossi et al also found that the preoperative application of these markers on LBC in suspicious samples can effectively distinguish lesions, which need immediate surgery from those which can be followedup [56,57].…”
Section: Discussionmentioning
confidence: 92%
“…The reported data demonstrated that the combined use of markers had a better sensitivity and specificity than using each of the markers separately. This may help distinguish indeterminate or suspicious samples with a low or high risk of malignancy, thereby enabling a more adequate surgical selection [52][53][54][55]. Fadda et al and Rossi et al also found that the preoperative application of these markers on LBC in suspicious samples can effectively distinguish lesions, which need immediate surgery from those which can be followedup [56,57].…”
Section: Discussionmentioning
confidence: 92%
“…68 Formalin-fixed paraffin-embedded cell blocks were created from the FNAB specimens and stained for Gal-3 using an ABC-detection system. Cytoplasmic staining of more than 10% of thyroid cells was required for Gal-3 positivity, and FNAB and pathological specimens underwent independent pathologist review.…”
Section: Immunocytochemical Studies Evaluating Gal-3 Expression In Nementioning
confidence: 99%
“…One flaw of this study was the relatively small number of indeterminate thyroid lesions included. Several other studies have looked at the accuracy of HBME-1 staining alone and found that HBME-1 ICC had a sensitivity of 79-87% and specificity of 83-96% in differentiating benign from malignant indeterminate thyroid nodules [66][67][68].…”
Section: Hbme-1 Cxcr4 Ck19 and Other Markersmentioning
confidence: 98%